REVEALING THE INVESTMENT VALUE OF PENANG HERITAGE PROPERTIES - Chin, Tiong Cheng; Yan, Bin Tan; Wai, Fang Wong; Kong, Seng Lai; Koh, Yu Xuan (PLANNING MALAYSIA, 2021)
Heritage buildings are a representation of historic features and the Malaysian culture. The intangible value of a heritage property comprises aesthetic quality, spiritual aspects, social functions, and its own uniqueness. Therefore, heritage properties have been seen to be moving away from traditional alternative investments, which are not covered by conventional real estate schemes. Additionally, the characteristics of heritage properties are expected to be seen as ‘art’, and they offer a highly beneficial diversification strategy with a relatively low correlation towards traditional assets classes. The Penang (Island) Heritage Property Price Index (PPHPPI) is estimated to be using a hedonic regression method. Based on the index, the heritage property records the highest quarterly returns and risk among the conventional assets considered in this study.